Pentastome assemblages of the Nile crocodile, Crocodylus niloticus Laurenti (Reptilia: Crocodylidae), in the Kruger National Park, South Africa - Junker, Kerstin; Calitz, Frikkie; Govender, Danny; Krasnov, Boris R; Boomker, Joop (Folia parasitologica, 2016)
Thirty-two specimens of the Nile crocodile, Crocodylus niloticus Laurenti (Reptilia: Crocodylidae), from the Kruger National Park, South Africa, and its vicinity were examined for pentastomid parasites during 1995 to 1999 and 2010 to 2011. Pentastomid parasites occurred throughout the year and were widespread in the study area with an overall prevalence of 97% and an overall mean abundance of 23.4 (0-81). Pentastome assemblages comprised six species in three sebekid genera: Alofia nilotici Riley et Huchzermeyer, 1995, A. simpsoni Riley, 1994, Leiperia cincinnalis Sambon, 1922, Sebekia cesarisi Giglioli in Sambon, 1922, S. minor (Wedl, 1861) and S. okavangoensis Riley et Huchzermeyer, 1995. The possible influence of host age, gender and geographic location (river system) on pentastome prevalence, abundance and species richness was investigated. Generally, neither host age, gender nor locality did affect infracommunities, likely because all hosts examined were adult or subadult and displayed comparable foraging behaviour, resulting in similar exposure pathways to fish intermediate hosts. Additionally, the longevity of pentastomids would contribute to accumulative infections as hosts mature. Structuring of pentastome assemblages was observed in as far as S. minor was the dominant species based on overall prevalence and abundance, followed by the equally common species S. cesarisi and L. cincinnalis. With an overall prevalence ranging from 34% to 41% and relatively low abundances, A. nilotici, A. simpsoni and S. okavangoensis form the rarer component of pentastome communities.
Keywords: Animals; Female; Prevalence; species richness; ženské pohlaví; South Africa; Alligators and Crocodiles; aligátoři a krokodýli; veřejné parky; Parasitic Diseases, Animal; Parks, Recreational; Jihoafrická republika; prevalence; parazitární nemoci u zvířat; Male; crocodilians; Sebekia; Pentastomida; mužské pohlaví; zvířata; Leiperia; abundance; Alofia